Quelles frontières pour les populations cholanes ? - Cédric Becquey (Ateliers d'Anthropologie)
Chol-language populations long held a central place in the Maya area, both geographically and culturally. The present landscape presents a quite different situation: with a geographic distribution that has become peripheral and a reduced demography, two of the three “surviving” Chol languages have already been classified as endangered by Unesco. The aim of this article is describe the principal phases of the evolution of the spatial boundaries of Chol populations through their stories, and to provide a few keys to understanding their movements. A study of this kind could certainly have been limited to historical data, but ethnological and linguistic observations make it possible to refine the parameters needed for the characterization of these boundaries, and to appreciate the interrelations these populations maintain with each other and with the “outer” world.